Transcending the modern mission tradition - Stroope, Michael W. (Regnum mini book series., 2020)
The urgent task of our day is to reimagine the church's witness to the Gospel of Jesus Christ. Yet, a mere attempt to rehabilitate or revise the modern mission tradition will not do. Mission as a rhetorical and conceptual framework is the problem. The ethos and spirit of modernity with its ideas of progress, individualism, commodification, and conquest are hardwired into mission, and thus, this modern mental model undermines faithful witness and service. Now is the time to transcend the modern mission tradition - to become pilgrim witnesses.